Axial-transverse coupled vortex-induced vibration characteristics of composite riser under gas-liquid two-phase internal flow. (1st June 2023) - Chang, Xueping; Song, Qiong; Qu, Congjia; Li, Yinghui; Liu, Jun
Abstract: In this paper, the dynamic behavior of axial (AX) and transverse coupled vortex-induced vibration (VIV) of composite riser under gas-liquid two-phase internal flow is studied. Firstly, based on Hamilton's principle, considering the structural characteristics of composite materials, gas-liquid two-phase internal flow, AX and transverse nonlinear coupling vibration and nonlinear external excitation, a more realistic VIV prediction model of composite riser is proposed. Compared with the existing experimental results, the validity of the model in this paper is verified, and it is found that the VIV prediction of the riser is more accurate when considering the AX and transverse coupling effects. Then, the effects of current velocity, liquid phase velocity, gas volume fraction and fiber orientation angle on the coupled VIV characteristics of gas-liquid mixed transport composite riser are studied. The results show that with the increase of current velocity, gas volume fraction and liquid phase velocity, the in-line (IL) vibration of the riser changes modally before the cross-flow (CF), but the fiber orientation angle has the opposite effect on this phenomenon. At the same time, when the two directions are in two different vibration modes, the vibration frequency in IL direction is obviously larger than that in CF direction. In addition, the riser AX vibration is almost unaffected by the parameters, but its vibration frequency is much larger than the other two directions, and the vibration center has shifted. We also find that the specific liquid phase velocity value will cause the chaotic vibration of the riser in the CF and IL directions, and the vibration displacements of the composite riser are almost equal in both directions. Highlights: A dynamic prediction model for axial-transverse coupled VIV of composite riser under gas-liquid two-phase internal flow is proposed. The fourth-order Runge-Kutta method is used to solve the nonlinear dynamics model. Considering axial-transverse coupled can predict the VIV characteristics of riser more accurately. Multiphase internal flow and composite materials have a great influence on the VIV dynamic characteristics of riser.